El discurso de género del profesorado de educación infantil: hablando acerca de la ética del cuidado. - Rodríguez Menéndez, Mª del Carmen; Torío López, Susana (Revista Complutense de Educación, 2006)
In this paper we will show some of the results of research which took place in the Principality of Asturias. Its purpose was finding out the gender discourses used by nursery teachers. Although we will not provide an exhaustive list of all the conclusions reached so far, we will put forward one of the aspects which has been developed throughout the investigation; that is, the differences observed by the teachers in boys and girls’ caring and supporting behaviours. In order to do so, we focus on the type of discourse related to the ethic of care. We consider it a tool which allows teachers to build a type of narrative in which boys and girls are presented as opposites, relational and different from one another.